An investigation of racing performance and whip use by jockeys in thoroughbred races. - David Evans (PLoS ONE, 2011)
Concerns have been expressed concerning animal-welfare issues associated with whip use during Thoroughbred races. However, there have been no studies of relationships between performance and use of whips in Thoroughbred racing. Our aim was to describe whip use and the horses' performance during races, and to investigate associations between whip use and racing performance. Under the Australian Racing Board (ARB) rules, only horses that are in contention can be whipped, so we expected that whippings would be associated with superior performance, and those superior performances would be explained by an effect of whipping on horse velocities in the final 400 m of the race. We were also interested to determine whether performance in the latter sections of a race was associated with performance in the earlier sections of a race. Measurements of whip strikes and sectional times during each of the final three 200 metre (m) sections of five races were analysed. Jockeys in more advanced placings at the final 400 and 200 m positions in the races whipped their horses more frequently. Horses, on average, achieved highest speeds in the 600 to 400 m section when there was no whip use, and the increased whip use was most frequent in the final two 200 m sections when horses were fatigued. This increased whip use was not associated with significant variation in velocity as a predictor of superior placing at the finish.